Relationship to the river: the case of the Muar River community - Abu Samah, Bahaman; Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (Science Publications, 2011)
Problem statement: Muar River which located in Johor, is an important river in Malaysia. Previously Muar River had a huge influence on the socio-economic status of the community. It has been used as the sources of income, protein and as well as the major mode of transportation for the community and traders. However, does the Muar River still has that influences on this modern day? The answer of this pertinent question will fulfill the main objective of this study which is to discover Muar River relationship with its surrounding community. Approach: In addition to relationship with the river, this quantitative study was conducted to determine the Muar River community agreement towards initiative to develop the river. A total of 300 respondents from 19 villages along Muar River were selected based on the simple random sampling. Results: Based on the analysis of the results, it can be concluded that Muar River still has a lot to offer to its surrounding community especially for the recreational activities (fish and prawn fishing). A large majority of Muar River community have a moderate and high level of agreement towards the river development. Further analysis performed revealed that income per month, number of household, age, distance to Muar River and period of staying in the areas had significant relationships with agreement towards river development. Conclusion/Recommendations: It is recommended that additional recreational facilities can be added, events at national and international level especially on fish and prawn fishing can be held at Muar River and campaign on the importance of river development and the danger of river pollution can be conducted.